2012
DOI: 10.1148/radiol.11110576
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Grade and Subtype of Meningiomas by Using Histogram Analysis of Diffusion-Tensor Imaging Metrics

Abstract: Purpose:To determine whether histogram analysis of diffusiontensor (DT) magnetic resonance (MR) imaging metrics, including tensor shape measurements, can help determine the grades and subtypes of meningiomas. Materials and Methods:The institutional review board approved this HIPAAcompliant study. Nine atypical, three anaplastic, and 39 typical meningiomas were retrospectively studied. The 39 typical meningiomas included one secretory meningioma and 11 fi broblastic, 11 transitional, 14 meningothelial, and two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
71
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(77 citation statements)
references
References 29 publications
2
71
4
Order By: Relevance
“…26 These findings can be explained by the presence of a large amount of collagen in fibroblastic subtypes. 25,33 It has been reported that the structure and orientation of extracellular matrix affect the anisotropy, but not the mean diffusivity 34 ; these results are consistent with ours. On the other hand, in brain metastases, neoplasm cells grow into the brain parenchyma in an expansive, noninfiltrating pattern.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…26 These findings can be explained by the presence of a large amount of collagen in fibroblastic subtypes. 25,33 It has been reported that the structure and orientation of extracellular matrix affect the anisotropy, but not the mean diffusivity 34 ; these results are consistent with ours. On the other hand, in brain metastases, neoplasm cells grow into the brain parenchyma in an expansive, noninfiltrating pattern.…”
Section: Discussionsupporting
confidence: 91%
“…The remaining region of FLAIR abnormality, outside of the IPR, was the distant peritumoral region. 12,23,25 The median FA and MD values were measured from the 3 regions. Data analysis tools, including image coregistration and segmentation, were implemented by using IDL (Exelis Visual Information Solutions, Boulder, Colorado).…”
Section: 2324mentioning
confidence: 99%
“…Previous studies investigated the roles of ADC and FA in subtyping meningiomas, but the results were controversial. 7,8,27 In the present study, we found that angiographic vascularity of meningiomas correlated with FA but not with ADC. Whereas ADC measures the average changes of water diffusivity, FA quantifies the diffusion anisotropy.…”
Section: Discussioncontrasting
confidence: 48%
“…5 DSC-PWI, on the other hand, measures T2*-weighted signal intensity loss that occurs dynamically over bolus injection of contrast medium, from which relative CBV, a quantitative marker of tumor angiogenesis, can be computed. 6 Both DTI 7,8 and DSC-PWI [9][10][11] had been reported to be useful in subtyping meningiomas. The microvessel area of meningiomas determined by histopathology was found to correlate with relative CBV derived from DSC-PWI.…”
mentioning
confidence: 99%
“…Additional indices that can be evaluated include skewness (the magnitude of symmetry of the histograms) and kurtosis (peakness of histograms) (Mori et al, 2008). Histogram analysis of DTI has been successfully used in brain tumor classification (Wang et al, 2012), investigation of clinical correlates in leukoariosis (Della Nave et al, 2007) and multiple sclerosis (Cercignani et al, 2001), differentiation between ischemic and non-ischemic patients with moyamoya disease (Mori et al, 2008), evaluation of traumatic brain inury (Marquez de la Plata et al, 2011), and so on. In this study, histogram analysis enabled a discrimination between the patients and normal subjects by its peak position, which is suggestive of its applicability in the evaluation of integrity of brain parenchyma in MDD.…”
Section: Discussionmentioning
confidence: 99%